Relationship between paramacular thinning, cerebral vasculopathy, and hematological risk factors in sickle cell disease - Orssaud, Christophe; Flamarion, Edouard; Michon, Adrien; Ranque, Brigitte; Arlet, Jean Benoit (Frontiers in Medicine, 2023)
Purpose To identify risk factors for sickle cell maculopathy due to hematological parameters (especially anemia and hemolysis) or cerebral vasculopathy. Methods This retrospective study was conducted at a Referral Center. The follow-up included optical coherent tomography/optical coherent tomography angiography, neuro-radiological imaging, and a hematological assessment (hemoglobin, hemoglobin S level, reticulocytes, mean corpuscular volume, bilirubin, and lactate dehydrogenase). Results Hundred and thirty-two sickle cell patients were included. Maculopathy was observed in 127 eyes of SS patients and 10 eyes of SC patients (p < 0.001), unrelated to peripheral retinopathy. Cerebral vasculopathy was more frequent in SS patients (p < 0.001) and was also associated with the presence of maculopathy (p = 0.049), and it was related to peripheral retinopathy (p < 0.001). All biological parameters significantly differed according to the genotype (p < 0.001) but not according to the presence of cerebral vasculopathy or maculopathy. In the multivariate analysis, reticulocytes and bilirubin were associated with the presence of cerebral vasculopathy and maculopathy. Conclusion The data obtained were consistent with the role of anemia or hemolysis markers in cerebral vasculopathy and macular involvement. As a trend of hemolysis appears to be a risk factor for these complications, this validates the use of preventive plasmapheresis in these patients.